Method of adjusting fuel equipment of a diesel locomotive by heat release feature under operating conditions - A. Yu. Kon’kov; A. I. Trunov; A. D. Gur’yanova (Вестник Научно-исследовательского института железнодорожного транспорта)
Diesel engines supply mechanical power to almost half of the locomotives of the Russian railways. To ensure the passport characteristics of a diesel locomotive during the entire period of operation, periodic adjustment of the fuel supply equipment is required. When adjusting it, it is necessary to ensure the balance of power between the diesel cylinders while not exceeding the protective parameters for the maximum combustion pressure and the temperature of the exhaust gases. This is achieved due to the identity of the cyclic fuel supply through the diesel cylinders and the close correspondence of the fuel supply advance angles between different cylinders. Existing methods of tuning the fuel supply equipment don’t allow performing the adjustment with the required accuracy or are too complicated and laborious to implement. This article proposes theoretically substantiated and experimentally tested method for adjusting the cyclic supply and the fuel supply advance angle based on the results of measuring the pressure in the cylinder through a standard indicator channel under operating conditions. The indicator diagram is used to calculate the characteristics of active heat release, which are used to determine the relative parameters featuring the state of the fuel supply equipment. The performed computational study showed that the proposed parameters are equivalent to the relative cyclic fuel supply and the relative advance angle of the fuel supply. An experimental check, carried out on a single-cylinder compartment of OCH18/22 engine with hydromechanical fuel equipment, showed the possibility of adjusting the fuel supply equipment by the proposed method with satisfactory accuracy.